Perancangan Home Disinfection Chamber untuk Pencegahan Virus COVID-19 - Rizki Pradipta Herrindra; Sulistyo Setiawan (Aliansi Desainer Produk Industri Indonesia (ADPII), 2022)
During the 2019 Coronavirus disease (hereinafter referred to as “COVID-19”) pandemic in 2020, many human activities have become limited, such as shopping for daily necessities. As a result, humans need products that can help carry out their activities in the midst of a pandemic. This study discusses the process of designing a cleaning tool that can be used before entering the home environment to prevent the virus from being carried from items exposed to the outside environment. This research is motivated by the need for a cleaning tool that can prevent the spread of the COVID-19 virus from items brought from outside the home. The products that are cleaned include shoes, electronic devices, and groceries purchased either through independent or online purchases. The purpose of this research is to produce a chamber design that can clean groceries and consumables quickly without damaging the packaging or products to be cleaned. The resulting design has a novelty value that is offered, namely a goods cleaning system using steam that can clean products from COVID-19 droplets. There is a theoretical basis used in the research, namely the use of disinfectants and antiseptics as a way to prevent the COVID-19 virus in housing. The design objectives were achieved through an online literature study analysis process accompanied by interviews and proofing the feasibility of the tools used with the Double Diamond design method. At the end of the process, a design is produced in the form of a final sketch and a 3D model of the disinfectant equipment brought from outside the house.